2019
DOI: 10.30773/pi.2019.06.17
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Oryza sativa L. Cyanidin-3-glucoside on the Cognitive Function in Older Adults with Subjective Memory Impairment

Abstract: ObjectiveCyanidin-3-glucoside (C3G), is a component of anthocyanin, have been considered to positively influence cognition and be beneficial for the prevention and treatment of dementia. We aimed to assess the safety and efficacy of cyanidin-3-glucoside-rich Oryza sativa L. (black rice) extract on cognitive function. MethodsA 12-weeks double-blind randomized, placebo controlled trial assessed safety and cognitive outcomes in participants with subjective memory impairment (n=48) following consumption of 6 black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…[ 47 ] Eight studies used a crossover design, [ 32,33,36,40,43–45,47 ] and 12 studies used a parallel design. [ 28–31,34,35,37–39,41,42,46 ] Blinding was not performed in one study, [ 40 ] three studies used single blinding, [ 33,35,45 ] and the other 16 studies were double‐blind. [ 28–32,34,36–39,41–44,46,47 ] In total, one study recruited healthy young adults aged between 18 and 25, [ 44 ] three studies included adults aged between 30 and 55, [ 34,36,43 ] and ten studies healthy adults over the age of 55 [ 30,32,33,39–42,45–47 ] while six studies recruited older adults with some form of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 47 ] Eight studies used a crossover design, [ 32,33,36,40,43–45,47 ] and 12 studies used a parallel design. [ 28–31,34,35,37–39,41,42,46 ] Blinding was not performed in one study, [ 40 ] three studies used single blinding, [ 33,35,45 ] and the other 16 studies were double‐blind. [ 28–32,34,36–39,41–44,46,47 ] In total, one study recruited healthy young adults aged between 18 and 25, [ 44 ] three studies included adults aged between 30 and 55, [ 34,36,43 ] and ten studies healthy adults over the age of 55 [ 30,32,33,39–42,45–47 ] while six studies recruited older adults with some form of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28–31,34,35,37–39,41,42,46 ] Blinding was not performed in one study, [ 40 ] three studies used single blinding, [ 33,35,45 ] and the other 16 studies were double‐blind. [ 28–32,34,36–39,41–44,46,47 ] In total, one study recruited healthy young adults aged between 18 and 25, [ 44 ] three studies included adults aged between 30 and 55, [ 34,36,43 ] and ten studies healthy adults over the age of 55 [ 30,32,33,39–42,45–47 ] while six studies recruited older adults with some form of cognitive impairment. [ 28,29,31,37,38,48 ] In total, 14 intervention arms included healthy participants ( n = 490), four included older adults with mild cognitive impairment (MCI) ( n = 290), one study included people with dementia ( n = 49), and one study included participants with subjective memory impairment (SMI) ( n = 48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from recent human studies investigating the effect of pigmented rice on lipid levels are inconsistent. Studies by Joo, et al, [32] Kim, et al, [33] Seesen [34] and Wang, [30] demonstrated a reduction in TC, LDL and TG following pigmented rice consumption, but were not significantly lower compared to control. Comparatively, a study by Syarief, et al [35] showed a significant decrease in TC, LDL and TG after the intervention compared to the control.…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…The consumption of anthocyanins-rich cherry juice (about 138 mg of anthocyanins/day) for 12 weeks has been shown to attenuate cognition losses in older adults with mild-to-moderate dementia Alzheimer’s type by improving cognitive tasks, such as verbal fluency and short and long-term memory [ 88 ]. Daily intake of purified anthocyanins (320 mg/day for 16 weeks), anthocyanins-rich black rice extract (19.08 mg of anthocyanins/day for 12 weeks), and blueberry anthocyanins (258 mg of anthocyanins/day for 16 weeks) also improved the cognitive performance in subjects with subjective memory impairment or mild cognitive impairment [ 81 , 86 , 87 ]. Anthocyanins can eliminate and block the action of free radicals in the brain, protect neurons susceptible to inflammatory processes, enhance existing neuronal function, increase cerebrovascular blood flow, and stimulate neurogenesis in areas of the brain related to cognition, among other mechanisms [ 15 , 88 ].…”
Section: Anthocyaninsmentioning
confidence: 99%